Regional differences in metastatic urothelial carcinoma of the urinary bladder patients across the United States SEER registries - Cano Garcia, Cristina; Tappero, Stefano; Piccinelli, Mattia Luca; Barletta, Francesco; Incesu, Reha-Baris; Morra, Simone; Scheipner, Lukas; Baudo, Andrea; Tian, Zhe; Saad, Fred; et al. (Canadian Urological Association Journal, 2023)
INTRODUCTION: Despite advances in treatment, metastatic urothelial carcinoma of the urinary bladder (mUCUB) is associated with high mortality and treatment risk. We tested for regional differences in mUCUB within a large-scale, population-based database. METHODS: Using the Surveillance, Epidemiology and End Results (SEER) database (2010– 2018), patient (age, sex, race/ethnicity), tumor (T-stage, N-stage, number of metastatic sites), and treatment (systemic therapy, radical cystectomy) characteristics were tabulated for mUCUB patients according to 11 SEER registries. Multinomial regression models and multivariable Cox regression models tested overall mortality (OM), adjusting for patient, tumor, and treatment characteristics. RESULTS: In 4817 mUCUB patients, registry-specific patient counts ranged from 1855 (38.5%) to 105 (2.2%). Important inter-regional differences existed for race/ethnicity (3–36% for others than non-Hispanic Whites), N-stage (28–39% for N1–3, 44–58% for N0, 8–22% for unknown N-stage), systemic therapy (38–54%), and radical cystectomy (3–11%). In multivariable analyses adjusting for these patient, tumor, and treatment characteristics, one registry exhibited significantly lower OM (SEER registry 10: hazard ratio [HR] 0.83) and two other registries exhibited significantly higher OM (SEER registry 9: HR 1.13; SEER registry 8: HR 1.24) relative to the largest reference registry (n=1855). CONCLUSIONS: We identified important regional differences that included patient, tumor, and treatment characteristics. Even after adjustment for these characteristics, important OM differences persisted, which may warrant more detailed investigation.